2008
DOI: 10.1128/iai.00228-08
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureusInduces Expression of Receptor Activator of NF-κB Ligand and Prostaglandin E2in Infected Murine Osteoblasts

Abstract: Osteomyelitis is an inflammatory disease of the bone that is characterized by the presence of necrotic bone tissue and increased osteoclast activity. Staphylococcus aureus is responsible for approximately 80% of all cases of human osteomyelitis. While the disease is especially difficult to treat, the pathogenesis of S. aureus-induced osteomyelitis is poorly understood. Elucidating the molecular mechanisms by which S. aureus induces osteomyelitis could lead to a better understanding of the disease and its progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 64 publications
2
65
0
Order By: Relevance
“…If neutrophils are deficient or inadequate to clear bacteria, the presence of bacterial toxins such as lipopolysaccharide (LPS) can induce prolonged and elevated levels of pro-inflammatory cytokines such as IL-1 and TNF-α [11]. Recent studies have shown that the principal causative organism for osteomyelitis, Staphylococcus aureus, is capable of upregulating production of several pro-inflammatory cytokines and inducing resorption of bone through RANK-L-mediated osteoclastogenesis, resulting in delayed or non-union of the fracture [8,12]. Similarly, formation of bacterial biofilms in a cutaneous wound has been shown to result in non-healing in a murine model [10].…”
Section: Clinical Significance and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…If neutrophils are deficient or inadequate to clear bacteria, the presence of bacterial toxins such as lipopolysaccharide (LPS) can induce prolonged and elevated levels of pro-inflammatory cytokines such as IL-1 and TNF-α [11]. Recent studies have shown that the principal causative organism for osteomyelitis, Staphylococcus aureus, is capable of upregulating production of several pro-inflammatory cytokines and inducing resorption of bone through RANK-L-mediated osteoclastogenesis, resulting in delayed or non-union of the fracture [8,12]. Similarly, formation of bacterial biofilms in a cutaneous wound has been shown to result in non-healing in a murine model [10].…”
Section: Clinical Significance and Managementmentioning
confidence: 99%
“…Infection is known to inhibit healing in several tissue types, including bone, gastrointestinal epithelium, and cutaneous epithelium [8][9][10]. Physiologic wound healing in response to injury occurs in four sequential and timed phases: hemostasis, inflammation, proliferation and repair, and remodeling.…”
Section: Clinical Significance and Managementmentioning
confidence: 99%
“…35,36 However, it is also possible that analysis of the membrane does not fully represent the profile of RANKL expression. Previous in vitro work in human and murine osteoblasts has shown that RANKL is upregulated in response to S. aureus infection, 18,19,37 and other studies have indicated that osteocytes, as opposed to osteoblasts or bone marrow stromal cells, are the dominant source of RANKL. 38 Because the objective of this study was to analyze mRNA expression profiles of cells in the induced membrane, the study primarily measures RANKL and OPG production by lymphocytes and stromal cells present in the induced membrane.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In vitro studies have shown the effects of S. aureus on local cells to be far reaching, such as decreasing osteoblast viability and differentiation, inhibiting the multilineage potential of mesenchymal stem cells (MSCs), increasing the production of resorptive factors and increasing the production of proinflammatory cytokines. [17][18][19] These effects are not conducive to the regeneration of bone, and thus, local antibiotic delivery is intended to eradicate bacteria to restore the regenerative capacity of local cell types. A study of the characteristics of an induced membrane generated in the presence of antibioticreleasing solid PMMA has demonstrated that antibiotics may also affect the thickness and vascularization of induced membranes in the absence of infection.…”
Section: Introductionmentioning
confidence: 99%
“…For orthopaedic infections, Staphylococcus aureus is the most commonly isolated agent, accounting for more than 1 . 2 of all infections [28]. In addition to increasing trends of antimicrobial resistance, the ability of bacteria to develop and persist in biofilms on implanted biomedical devices is recognized as a major factor contributing to chronic relapsing infections and nonosseous union [4,35,42,44,48,49].…”
Section: Introductionmentioning
confidence: 99%